DHRCA: A Design of Security Architecture Based on Dynamic Heterogeneous Redundant for System on Wafer - Bo Mei; Zhengbin Zhu; Peijie Li; Bo Zhao (IET Information Security)
System on Wafer (SoW) based on chiplets may be implanted with hardware Trojans (HTs) by untrustworthy third-party chiplet vendors. However, traditional HTs protection techniques cannot guarantee complete protection against HTs, which poses a great challenge to the hardware security of SoW. In this paper, we propose a computing architecture based on endogenous security theory—dynamic heterogeneous redundant computing architecture (DHRCA) that can tolerate and detect HTs at runtime. The security of our approach is analyzed by building a generalized stochastic coloring petri net (GSCPN) model of DHRCA. The simulation results based on the GSCPN model show that our method can improve the system security probability to 0.8690 and the system availability probability to 0.9750 in the steady state compared with typical triple-mode redundancy and runtime monitoring methods. Furthermore, the impact of different attack and defense strategies on system security of different methods is simulated and analyzed in this paper.